Late-Onset Sepsis in very Low Birth Weight Infants: A Brazilian Neonatal Research Network Study - Rugolo, Ligia Maria Suppo de Souza [UNESP]; Bentlin, Maria Regina [UNESP]; Mussi-Pinhata, Marisa; Branco de Almeida, Maria Fernanda; Andrade Lopes, Jose Maria de; Martins Marba, Sergio Tadeu; Fiori, Humberto Holmer; Procianoy, Renato Soibelmann; Leone, Clea Rodrigues (Oxford Univ Press, 2014)
Background: Late-onset sepsis (LOS) is an important cause of morbidity and mortality in very low birth weight (VLBW) infants.Aim: To determine the incidence, risk factors and etiology of LOS.Methods: LOS was investigated in a multicenter prospective cohort of infants at eight public university neonatal intensive care units (NICUs). Inclusion criteria included inborn, 23-33 weeks of gestational age, 400-1499 g birth weight, who survived >3 days.Results: Of 1507 infants, 357 (24%) had proven LOS and 345 (23%) had clinical LOS. Infants with LOS were more likely to die. The majority of infections (76%) were caused by Gram-positive organisms. Independent risk factors for proven LOS were use of central venous catheter and mechanical ventilation, age at the first feeding and number of days on parenteral nutrition and on mechanical ventilation.Conclusion: LOS incidence and mortality are high in Brazilian VLBW infants. Most risk factors are associated with routine practices at NICU.
Keywords: Sepsis; infection; newborn infant; very low birth weight; premature